The influence of theory of planned behaviour on work-life extension among healthcare professionals in Nigeria: Data screening and preliminary analysis - Nasiru, Muhammad Anka; Md Dahlan, Nuarrual Hilal (2020)
The acutescarcity of health professionals, especially registered nurses and registered midwivesin Nigeria has provoked the government to suggest a policy to extend thesehealthcare providers’ work-life after retirement. Nonetheless, not much is known about the intention and subsequent preparation among the selected healthcare providers to extend their work-life after retirement. This study’s objective was to conduct data screening and preliminary analysis of somecarefully chosentheory of planned behaviour constructs (attitude, subjective norm, perceived behavioural control, intention, and preparation). The study used a cross-sectional survey and a simple random sampling technique to gather data. A total of 515 questionnaires were sent to the prospective respondents, and 446 filled and usable questionnaires were retrieved and used for further analysis. The data was screened and cleaned using statistical package for social science (SPSS) v24 to fulfil multivariate analysis’s fundamental assumptions, emphasizing reliable, acceptable, error-free data, and a clear interpretation of results. Explicitly, the current study carried out data screening through assessing response rate, missing values, and outliers—also, the study screens normality, multicollinearity, nonresponse bias, and common method variance. The outcome of the study demonstrated the dataset satisfied all the conditions for further multivariate analysis.The study’s findings will be significant to researchers, health professionals, and policymakers vested with the responsibility of ensuring Nigeria’s society’s health and wellbeing. Thus, this paper recommends that the current dataset explore the association between the predictor variables and the criterion variable(s).